2013
DOI: 10.1016/j.aprim.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de la transición a la maternidad: estudio fenomenológico en la provincia de Barcelona

Abstract: Dynamic groups should be contextualised according to the perceived needs of the mothers, and other family members should be allowed to participate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…This contradiction of feelings has been reported in studies that showed that in many cases, the reality of breastfeeding did not reflect the expectations that mothers had about the process (Cortés & Díaz, 2019;Morns et al, 2021). In view of idea that breastfeeding is a natural process, these studies bring to light a confrontation between the reality of the mothers' struggle and cultural construction that breastfeeding is a problem-free process (Berlanga et al, 2013;Cortés & Díaz, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…This contradiction of feelings has been reported in studies that showed that in many cases, the reality of breastfeeding did not reflect the expectations that mothers had about the process (Cortés & Díaz, 2019;Morns et al, 2021). In view of idea that breastfeeding is a natural process, these studies bring to light a confrontation between the reality of the mothers' struggle and cultural construction that breastfeeding is a problem-free process (Berlanga et al, 2013;Cortés & Díaz, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…We finally asked, “If women, because of their work schedule, do not manage reconciling work and family needs, they feel bad and guilty (in other words, if they cannot take part in activities with the children, cannot take care of them or accompany them).” This item was based on works by Rodríguez et al (2009) and Berlanga et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…The focus groups were led by another woman physiotherapist (B.S.-S.), a university professor, who also specialized in women's health and was experienced in qualitative research interviews. She was not connected with the study in order to achieve the appearance of a new perspective [20], and the participants did not know her. All the interviews began with the presentation of the objective of the study, the guarantee of the confidentiality of the contributions and the request for permission to record the audio of the interviews.…”
Section: Research Team and Reflexibilitymentioning
confidence: 99%